Effect of different staircase and exit layouts on occupant evacuation. (October 2019) - Lei, Wenjun; Tai, Chuanmin
Highlights: Effects of the location of staircase and exit on occupant evacuation were investigated. When an exit was located facing the staircase, the evacuation time was lower. The locations of staircases had a minimal effect on evacuation. With an equivalent exit width, the evacuation efficiency of a building with two exits was higher. Abstract: In the process in which people enter and exit buildings, available exits in buildings are not effectively utilized and cause overcrowding at other exits. Therefore, the effect of the locations of staircases and exits on occupant evacuation was investigated in this paper. The FDS+Evac software package was used to quantify the evacuation process. Four scenarios were simulated to investigate the detailed properties of evacuation. The results revealed that the locations of staircases had a minimal effect on evacuation. When the staircases were located in the middle of a building, flow stratification occurred. With stratification, the flow rate is not constant throughout the evacuation process. Two or more evacuation stability stages exist. The evacuation flow rate curve resembles a ladder. Stratification in the flow rate causes increasing panic during crowd evacuation as people in the rear of a building cannot locate the target that can be followed in front of them. With an equivalent exit width, the evacuation efficiency of a building with two exits was higher, and the evacuation time was shorter. When an exit was located facing the staircases, the evacuation time was lower, and the flow rate of the occupants was relatively stable. Therefore, buildings should be designed with exits facing the staircases. If feasible, large staircases should be replaced with two identical sets of staircases. These measures will facilitate evacuation.